Ethyl pyruvate is a novel anti-inflammatory agent to treat multiple inflammatory organ injuries. Issue 1 (December 2016) - Yang, Runkuan; Zhu, Shengtao; Tonnessen, Tor
Abstract Ethyl pyruvate (EP) is a simple derivative of pyruvic acid, which is an important endogenous metabolite that can scavenge reactive oxygen species (ROS). Treatment with EP is able to ameliorate systemic inflammation and multiple organ dysfunctions in multiple animal models, such as acute pancreatitis, alcoholic liver injury, acute respiratory distress syndrome (ARDS), acute viral myocarditis, acute kidney injury and sepsis. Recent studies have demonstrated that prolonged treatment with EP can ameliorate experimental ulcerative colitis and slow multiple tumor growth. It has become evident that EP has pharmacological anti-inflammatory effect to inhibit multiple early inflammatory cytokines and the late inflammatory cytokine HMGB1 release, and the anti-tumor activity is likely associated with its anti-inflammatory effect. EP has been tested in human volunteers and in a clinical trial of patients undergoing cardiac surgery in USA and shown to be safe at clinical relevant doses, even though EP fails to improve outcome of the heart surgery, EP is still a promising agent to treat patients with multiple inflammatory organ injuries and the other clinical trials are on the way. This review focuses on how EP is able to ameliorate multiple organ injuries and summarize recently published EP investigations. Graphical Abstract The targets of the anti-inflammatory agent EP